Whole-genome analysis of coxsackievirus B3 reflects its genetic diversity in China and worldwide - Qian Yang; Dongmei Yan; Yang Song; Shuangli Zhu; Yun He; Zhenzhi Han; Dongyan Wang; Tianjiao Ji; Yong Zhang; Wenbo Xu (Virology Journal, 2022)
Abstract Background Coxsackievirus B3 (CVB3) has emerged as an active pathogen in myocarditis, aseptic meningitis, hand, foot, and mouth disease (HFMD), and pancreatitis, and is a heavy burden on public health. However, CVB3 has not been systematically analyzed with regard to whole-genome diversity and recombination. Therefore, this study was undertaken to systematically examine the genetic characteristics of CVB3 based on its whole genome. Methods We combined CVB3 isolates from our national HFMD surveillance and global sequences retrieved from GenBank. Phylogenetic analysis was performed to examine the whole genome variety and recombination forms of CVB3 in China and worldwide. Results Phylogenetic analysis showed that CVB3 strains isolated worldwide could be classified into clusters A–E based on the sequence of the entire VP1 region. The predominant CVB3 strains in China belonged to cluster D, whereas cluster E CVB3 might be circulated globally compared to other clusters. The average nucleotide substitution rate in the P1 region of CVB3 was 4.82 × 10–3 substitutions/site/year. Myocarditis was more common with cluster A. Clusters C and D presented more cases of acute flaccid paralysis, and cluster D may be more likely to cause HFMD. Multiple recombination events were detected among CVB3 variants, and there were twenty-three recombinant lineages of CVB3 circulating worldwide. Conclusions Overall, this study provides full-length genomic sequences of CVB3 isolates with a wide geographic distribution over a long-term time scale in China, which will be helpful for understanding the evolution of this pathogen. Simultaneously, continuous surveillance of CVB3 is indispensable to determine its genetic diversity in China as well as worldwide.